Assessing the causes and effects of delay and disruption in construction projects in Malaysia - Sohu, Samiullah; Md Kassim, Tahara Ramadzan; Mustafa, A.; Arshad, M. U.; Nagapan, Sasitharan (Sciendo, 2024)
Construction projects often face challenges while execution such as delays and disruptions. Thus, Research studies are being carried out to managing the potential risks such as technical, economical, legal, social, commercial, financial, resource and construction that might arise from delays as well as from disruptions. The prime aim of this research is to identify the causes and effects on construction projects due to delays and disruptions. For the data collection, a descriptive study designed to obtain causes that effected construction projects due to delays and disruptions from regulatory bodies clients, consulting and construction firms. Relative importance index (RII) methodology is utilized for identification of important parameters related to delay and disruptions. In this study random sampling technique are utilized for selection of respondents. For data collection literature review and questionnaires survey techniques are received from respondents. The results obtained from this research study revealed that poor project management, funding problems, design changes, delay in payment to contractors, information delays, disagreement on the valuation of work done and compensation issues are identified as main causes for delays and disruptions. In addition to that, the results mentioned that, major effects include cost overrun, time overrun, negative social impact, disputes and idling resources due to delays and disruptions. The study summarizes that there are few causes that effected delays and disruptions that put projects at risk and impacted on project performance. Therefore, it is suggested that prime focus should be kept on sufficient budget of construction, timely issuing of information, design completion and rational project management skills during procurement processes for betterment.